2006
DOI: 10.1002/eji.200526311
|View full text |Cite
|
Sign up to set email alerts
|

Migration of immature mouse DC across resting endothelium is mediated by ICAM‐2 but independent of β2‐integrins and murine DC‐SIGN homologues

Abstract: Immature dendritic cells (DC) reside in tissues where they initiate immune responses by taking up foreign antigens. Since DC have a limited tissue half-life, the DC pool in tissues has to be replenished constantly. This implies that precursor/immature DC must be able to cross non-activated endothelium using as yet unknown mechanisms. Here we show that immature, but not mature bone marrow-derived murine DC migrate across resting endothelial monolayers in vitro. We find that endothelial intercellular adhesion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…These combined outcomes indicate that migration of APC to CD18 −/− PLN is intact. This is consistent with most, but not all (19,33), studies showing that transendothelial migration of mouse (34) and human (35) DC can be independent of β2 integrins. Similarly, migration of CD18 −/− DC to skin at sites of acute contact dermatitis in mice is normal (12).…”
Section: Discussionsupporting
confidence: 89%
“…These combined outcomes indicate that migration of APC to CD18 −/− PLN is intact. This is consistent with most, but not all (19,33), studies showing that transendothelial migration of mouse (34) and human (35) DC can be independent of β2 integrins. Similarly, migration of CD18 −/− DC to skin at sites of acute contact dermatitis in mice is normal (12).…”
Section: Discussionsupporting
confidence: 89%
“…This is partly due to the fact that mouse does not have the ICAM-3 homologue in its genome [40]. Moreover, mouse SIGNRs 1, 3 and 5 do not interact with mouse ICAM-2 and do not support ICAM-2 mediated transmigration of immature DCs across resting endothelium [41]. SIGNR5 plays no role in T cell-DCs interactions and did not bind to pathogens known to interact with hDC-SIGN [42].…”
Section: Discussionmentioning
confidence: 99%
“…Some information may be gleaned from in vitro experiments. For example, a recent study found a role for the IgSF molecule ICAM-2 in the transmigration of immature DCs across endothelial monolayers (Wethmar et al, 2006). …”
Section: Traffic To Non-lymphoid Tissuesmentioning
confidence: 99%